ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI CASH HOLDING PADA PERUSAHAAN INDUSTRI SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2018 - Monik Sari; Intan Zoraya (Management Insight: Jurnal Ilmiah Manajemen, 2021)
Cash is used to support the smooth running of operations and maintain company liquidity. The purpose of this study was to examine the effect of cash flow, net working capital, leverage, firm size and growth opportunity on company cash holding. The object of this research is the consumer goods sector industrial companies listed on the Indonesia Stock Exchange in 2009-2018. This research uses purposive sampling technique. The sample in this study were 12 companies based on the regression analysis criteria that had been determined using the pooled last square approach in the Eviews 9.0 program. The results of this study indicate that cash flow has a significant negative effect on cash holding, networking capital has a significant positive effect on cash holding, while leverage has a positive and insignificant effect on cash holding, firm size and growth opportunity has a negative and insignificant effect on cash holding.